Optimization of Sanitation Facilities to Support Open Defecation Free (ODF) Programs in Dusun 13 Desa Percut Kecamatan Percut Sei Tuan - Hasibuan, Novrida Harpah; Suryati, Isra; Khairani, Fitri; Dalimunthe, Nurul Ika Putri (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Lack of access to proper sanitation is a major risk factor for infectious diseases such as cholera, diarrhea, dysentery, hepatitis A, typhoid and polio. The Community-Based Total Sanitation Program in the first pillar of Stop Open Defecation aims to change people's lifestyles by using proper sanitation. However, the program has not run evenly. One of the areas that has not yet received the results of the policy is Dusun 13, Percut Village, Percut Sei Tuan, Deli Serdang Regency, North Sumatra which is a coastal area. This community service was able to provide proper sanitation facilities and socialization of healthy lifestryle to the community especially housewife in this area. The construction of sanitation facilities are two bathrooms with a size of 2 x 1.5 m with closets in each room, a septic tank with a capacity of 15 people basen on Indonesia Standard with number 2398 : 2017, tested the water quality, and installed a water pump. Socialization to implemented healthy lifestyle properly done with 20 participants as housewife in this area. This community service is expected to improve the quality of life, prevent the transmission of waterborne diseases and prevent groundwater contamination